2002
DOI: 10.4102/sajip.v28i2.45
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising And Operationalising Work Versus Career Salience

Abstract: Career salience was defined and operationalised by Greenhaus in 1971. His scale and conceptualisation of this construct have attracted critical review. Numerous authors have tested various alternative conceptualisations of career salience. However, these approaches have tended to neglect some of the valuable ideas in Greenhaus’ original construct. The present authors suggest that career salience constructs and measures have also been contaminated with an associated but unrecognised construct, namely, work sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 34 publications
4
21
0
Order By: Relevance
“…This finding supports similar results obtained by Allen and Ortlepp (2000). An increase in work-role salience (expressed for example through greater participation in, commitment to, or stronger value expectations of the work role) is likely to lead to an increase in career salience.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This finding supports similar results obtained by Allen and Ortlepp (2000). An increase in work-role salience (expressed for example through greater participation in, commitment to, or stronger value expectations of the work role) is likely to lead to an increase in career salience.…”
Section: Discussionsupporting
confidence: 80%
“…c) The Work Salience Questionnaire (WSQ) and Career Salience Questionnaire (CSQ) of Allen and Ortlepp (2000) were used to assess work salience and career salience respectively. Recent research found support for the scales' face, content, convergent and divergent validity, as well as internal reliability of 0.83 for the CSQ and 0.80 for the WSQ (Allen & Ortlepp, 2000). Convergent validity of the scales was established using Greenhaus' (1971) Career Salience Scale.…”
Section: Measuring Instrumentsmentioning
confidence: 99%
“…The salience of alertness behaviors refers to the individual’s perceived importance or prominence of the behavior(s). Draft items for assessing salience were developed using prior research, which focused on measuring the salience of one’s career (Allen et al, 2002). Allen and Ortlepp collated items from previous research and developed two scales, one for measuring career salience and one for measuring work salience.…”
Section: Methodsmentioning
confidence: 99%
“…Respondents were asked to indicate the importance that each of ten items would be in their decision to accept a potential job or stay in a job, on a five-point scale (1 ¼ not at all important, 5 ¼ absolutely essential). Career salience was measured using Allen and Ortlepp's (2002) single-factor measure of the importance of career to one's life (a ¼ 0.86). The original 11-item measure was reduced based on Allen and Ortlepp's factor analysis.…”
mentioning
confidence: 99%